THE EMERGENCE OF FLUOROQUINOLONES RESISTANCE AMONG MDR-TB PATIENTS AT A TERTIARY CARE FACILITY IN SIALKOT - KHAN, AW; SAEED, H; TARIQ, A; ASLAM, A (Biological and Clinical Sciences Research Journal, 2022)
Pakistan is one of the countries that has a very high rate of multidrug-resistant tuberculosis (MDR-TB). The rising rate of drug resistance can be linked to several issues, including the private sector that is inadequately regulated, an increase in the number of prescribed antibiotics, and the practice of self-medication. A national anti-tuberculosis medication resistance survey found a high prevalence of fluoroquinolone resistance in multidrug-resistant tuberculosis patients. The purpose of this study was to evaluate fluoroquinolone resistance among multi drugs resistant TB patients. This study looked at the records of drug susceptibility testing, known as DST, for a total of 276 patients at Govt. Allama Iqbal memorial teaching hospital Sialkot, who was receiving treatment for tuberculosis. Eight-six patients fulfilling the inclusion criteria were included in the final analysis. The incidence of fluoroquinolone (ofloxacin) resistance was investigated, and its association with demographic factors and previous TB treatment categories was studied. When assessing fluoroquinolone resistance on DST, 44 (51.2%) patients resisted levofloxacin and 11 (12.8%) with moxifloxacin. In our study, the fluoroquinolones resistance was not statistically different in Cat-1 and Cat-2 patients. Similarly, age and gender also showed no significant difference in resistance to moxifloxacin and levofloxacin in MDR-TB patients. An alarmingly high percentage of MDR-TB infections showed resistance to fluoroquinolones. Based on our findings, it may be necessary to reevaluate current treatment recommendations for multidrug-resistant tuberculosis. There is an immediate need for stricter pharmacy regulations and better responsible involvement of private healthcare providers.